Oxidative stress-induced inflammatory responses and effects of N-acetylcysteine in bovine mammary alveolar cells. Issue 4 (20th November 2017) - Bae, Hyojin; Jeong, Chang Hee; Cheng, Wei Nee; Hong, Kwonho; Seo, Han Geuk; Han, Sung Gu
Abstract : Bovine mastitis, an inflammation of the udder, results in reduced milk production and poor milk quality. Mastitis is usually, but not always, a response to pathogen infection. High milk yield can produce oxidative stress in the mammary tissue. High milk yield is also known to be associated with bovine mastitis. Thus, in the current study, we hypothesised that oxidative stress increases inflammatory responses in bovine mammary cells. To examine the hypothesis, we produced cellular oxidative stress and investigated resulting inflammatory responses in bovine mammary alveolar cells (MAC-T). To produce oxidative stress, cells were treated with the reactive oxygen species (ROS; e.g., superoxide anion)-producing agent, menadione (MD; 0–10 µm ; 6 h). To ensure the ROS-induced responses, cells were pretreated with an antioxidant NAC (0–10 mm ; 1 h). Results showed that MD elevated intracellular ROS levels and protein expression of cyclooxygenase-2 (COX-2), a biomarker of inflammation. Pretreatment of cells with NAC attenuated MD-induced COX-2 expression by scavenging intracellular ROS and enhancing intracellular glutathione levels. MD-induced COX-2 expression was mediated by activation of extracellular signal receptor-activated kinase 1/2 (ERK1/2), Akt, and nuclear factor-kappa B (NF-κB). NAC attenuated activation of these intracellular signalling molecules. Treatment of cells with pharmacological inhibitors for ERK1/2, Akt, and NF-κB confirmed the association of these signalling pathways in MD-induced COX-2 expression. These results support our hypothesis that oxidative stress, which is found in high-yielding dairy cows, can produce cellular inflammation in bovine mammary alveolar cells and prevention of oxidative stress can attenuate such pathological responses. This may be relevant for cases of clinical mastitis for which no pathogen can be isolated.